PENERAPAN LEARNING CYCLE 5E DENGAN MENGGUNAKAN MEDIA MANIPULATIF UNTUK MEMAHAMKAN SEGI EMPAT BAGI SISWA KELAS VII SMPK FRATERAN NDAO ENDE - Agnes Pendy (Program Studi Pendidikan Matematika, 2018)
The purpose of this research is to describe the steps Learning Cycle 5E by using manipulatve media that can explain quadrangle for students of class VII SMPK Frateran Ndao Ende. This research used a descriptive-qualitative approach. The subjects were students of class VII-4 SMPK Frateran Ndao Ende. Research subjects are given the test relating to the understanding and interviewed with Learning Cycle 5E aided manipulative media to can explain quadrangle..The results showed that the application of Learning Cycle 5E can explain quadrangle assisted manipulative media. This can be demonstrated by an increase in the percentage activity teachers of 82% for 86,5%, activity students of 78,3% for 84,8%, and comprehension test scores of students of class VII-4 of 71% for 87,1%.